Introduction: ethics, aesthetics, and cultural debates surrounding narratives of scandal and shock - De Muijnck, Deborah; Vanhanen, Tero Eljas (De Gruyter, 2026)
Scandals and the shocks they provoke have long shaped the cultural, political, and aesthetic imagination of the Western world. They expose and disrupt social norms, yet by doing so, they make those very norms visible and subject to renegotiation. This special issue, Narratives of Scandal and Shock: Transgression, Media, and Cultural Response, explores how scandalous narratives emerge, circulate, and transform across literary, historical, and medial contexts. Drawing on narrative theory, literary studies, and cultural history, the contribution examine how transgressive acts, authors, and texts incite public outrage and fascination, compelling societies to re-evaluate morality, authorship, and cultural identity. The issue investigates how scandal operates as both an aesthetic strategy and a social mechanism—arresting thought through shock, provoking affective engagement, and at times catalyzing change. Case studies range from classical and nineteenth-century controversies to contemporary debates surrounding #MeToo, autofiction, and transgressive literature, to name just a few examples. Together, these essays demonstrate that scandal and shock are not mere disruptions but productive forces in the ongoing negotiation of cultural values and artistic expression.